International Terrorism: Agenda Propaganda United States and its Views by Islam - Ali Alfurqo (International Journal of Science and Society, 2020)
The study of terrorism, particularly international terrorism more prominent after the September 11th 2001. Now even the agenda almost every international meeting is always related or associated with terrorism issues. Not infrequently, this raises the presumption that the agenda of terrorism is closely associated with the propaganda agenda of the United States, because the United State currently taking part in many international issues. As a comparison from another perspective, when terrorism many associated with Islamic movements, it is important also to see, how to actually study the terrorism in the eyes of Islam.